The enemy of my enemy : the alarming convergence of militant Islam and the extreme right - Michael, George, 1961- (Lawrence, Kan. : University Press of Kansas, 2006)
In the violent world of radical extremists, "the enemy of my enemy is my friend." In this provocative study, George Michael reveals how that precept plays out in the unexpected bonding between militant Islam and the extreme right in America and Europe. At first glance these two groups would seem to share little if any common ground. Why would various neo-Nazis, Holocaust deniers, white separatists, and antigovernment radicals find themselves attracted to movements such as Al Qaeda, Hezbollah, Hamas, and Egyptian Islamic Jihad? After all, the extreme right's racist and radical Christian segments tend to deride and exclude all nonwhites and non-Christians, while Islamic fundamentalists angrily denounce all non-Muslims, especially Americans, as infidels. Nevertheless, as Michael shows, they have developed strikingly similar critiques on such issues as American foreign policy, the media, modernity, and the New World Order. The first book to focus on the growing linkage between these two movements, The Enemy of My Enemy analyzes the histories and ideologies guiding these disparate groups, clarifies the nature of their mutual appeal, and shows how the Internet and globalization have made increased interaction possible. Michael notes that one particularly dominant thread running throughout both camps is a fervent anti-Semitism, accompanied by strong pro-Palestinian views, anger over Israel's influence on American policymakers, and opposition to the Iraq War and the U.S. presence in the Middle East. Michael also speculates on how the so-called War on Terror might unfold if this unexpected and alarming convergence grows stronger. While the thought of Americans assisting or fighting alongside Islamic militants-in America-sounds utterly far-fetched, Michael points out that some members of the extreme right have publicly expressed admiration for Al Qaeda's audacious attacks on 9/11. Daring to consider the unthinkable, Michael provides an insightful and sane look at the possibilities for collaboration between these groups and raises a quiet but clear alarm for anyone concerned about America's future.
1. Introduction -- 2. The contemporary extreme right -- 3. The development of militant Islam and Arab nationalism -- 4. Militant Islam in the United States -- 5. Interaction between the extreme right and Islamic/Arab extremists -- 6. The U.S. government's response to political extremism and terrorism -- 7. The role of nongovernmental organizations in the aftermath of 9/11 -- 8. How the extreme right views the current crisis -- 9. How militant Islam views the current crisis -- 10. Prospects for cooperation between militant Islam and the extreme right -- 11. Conclusion.
Includes bibliographical references (p. 365-375) and index.
The Roger Griffin ComFas Collection
Keywords: Terrorism -- United States; Terrorism -- Religious aspects -- Islam; Right-wing extremists -- United States; Islamic fundamentalism; Religious militants